How does environmental regulation affect the cobalt supply chain resilience: empirical evidence from cross-border data - Cheng, Penghong; Zhou, Wenxiao; Chen, Lu; Bai, Yongliang; Sun, Han (Frontiers in Environmental Science, 2026)
Constrained by resource endowment, the traditional cobalt supply chain model oriented towards efficiency maximization struggles to effectively respond to sudden risks such as supply disruptions. Therefore, enhancing cobalt supply chain resilience (CSCR) is becoming a critical issue for the sustainable development of the mineral industry sector. However, it remains unclear whether environmental regulation (ER) has an impact on CSCR. This study constructs a theoretical framework for analyzing the influence of ER on CSCR and employs econometric methods to conduct an empirical examination using a sample of 22 representative countries (regions) with accessible data. The research findings are as follows: (1) ER can significantly enhance CSCR, and this conclusion remains valid after a series of robustness tests. (2) ER functions through three channels: First, it drives green technological innovation and enhances the internal production capacity of the supply chain. Second, it guides the diversification of import sources and optimize the structure of the supply chain network. Third, it attracts high-quality foreign direct investment, leverage capital spillover effects, and enhance the vitality of the supply chain system. (3) Political stability plays a positive moderating role in the above process: A stable institutional environment can enhance the resilience dividend of ER. (4) the impact of ER is heterogeneous across different economic scales and the locations of supply chain. The research provides a new resilience theoretical perspective for understanding the relationship between environmental policies and resource security, and offers data support for coordinating ecological environment governance and stable mineral supply.